Evaluasi Sistem Distribusi Listrik IPAM Menggunakan Fuzzy Decision Making Berbasis Kualitas dan Rugi Daya - Syam Abiansyah Pradana Sakti; Joko Joko; Tri Rijanto; Endryansyah Endryansyah (INDO PUBLISHING, 2026)
This study analyzes the electric power quality and operational conditions of induction motors at a Water Treatment Plant (IPAM) using the Fuzzy Decision Making (FDM) method. The analyzed parameters include voltage, voltage harmonics, current unbalance, power factor, and stator copper losses in Distribution Motors 1, 4, and 5. The analysis results show that the average voltage harmonics is 1.37%, which remains within the IEEE 519-1992 limit of 3%. The average current unbalance for all motors is 2.75%, within the IEC 60038 limit of 5%. Voltage levels experience an average overvoltage of 4.72%, staying within the ANSI C84.1 – 2020 limit of 5%. The average power factor is 0.833, which is below the SPLN D3.004-1:2010 standard minimum of 0.85. Stator copper losses for all motors average 1.928%, well within the IEC 60034-30-1 limit of 5.6%. The Mamdani fuzzy inference system, utilizing 48 IF-THEN rules, produces a single condition index for each motor. The results indicate that Distribution Motor 1 has an average index of 82.9, Motor 4 an average of 86.2, and Distribution Motor 5 an average of 82.6, all of which fall within the 'Normal' category.